CHARACTER EDUCATION MANAGEMENT AT THE MUHAMMADIYAH MODERN BOARDING SCHOOL MUHAMMADIYAH BOARDING SCHOOL YOGYAKARTA FOR IMPROVING STUDENT ACHIEVEMENT - Nurdin; Gofur Ahmad; Rabiatul Adawiyah (International Journal of Teaching and Learning, 2026)
This study aims to conduct an in-depth analysis of the implementation of character education management at the Muhammadiyah Modern Boarding School (PPM MBS) Yogyakarta to improve student achievement. Character education is understood as an integrative process that internalises the six values upheld by PPM MBS Yogyakarta—sincerity, honesty, discipline, kinship, togetherness, and independence—through a boarding school-based education system. This study employs a qualitative approach with a case study design. The research subjects included the head of the senior high school, the deputy head for boarding school affairs, the head of the boarding school department, the discipline officer, the IPM (Islamic Student Association) mentor officer, the language officer, the tahfiz  and worship officer, the head of the boarding school section (   ), senior high school teachers, students, and parents. Data collection techniques involved in-depth interviews, participatory observation, and document analysis. Data analysis utilised an interactive model comprising data reduction, data presentation, and drawing conclusions, with triangulation of sources and methods to ensure data validity. The research findings indicate that character education management in boarding schools is implemented in an integrated manner through the formal curriculum, boarding life guidance, the cultivation of religious practices, the exemplary conduct of educators, and school culture. The implementation of this character education not only contributes to the formation of students’ personalities and attitudes but also has a positive impact on the improvement of academic and non-academic achievements. Key supporting factors include the boarding school system, the exemplary conduct of educators, and the religious environment. Meanwhile, inhibiting factors stem from the heterogeneity of students’ backgrounds and limitations in initial adaptation. This study produced an operational model of boarding school-based character education at senior secondary level that is practical and sustainable.